Tinjauan Implementatif Manajemen Seleksi Kepala Madrasah terhadap PMA No. 24 Tahun 2018 - Fauziah, Iis; Hermawansyah, Hermawansyah; Junaidin, Junaidin (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to analyze the concept of Islamic educational institution management in the selection of madrasah principals based on the implementation of Minister of Religious Affairs Regulation (PMA) Number 24 of 2018. This study uses a qualitative approach with an integrative literature review method, analyzing regulatory documents, scientific articles, books, and reports related to Islamic education management, leadership, merit-based selection, and policy implementation. The data were analyzed descriptively and analytically through data reduction, data presentation, and conclusion drawing. The findings show that, normatively, PMA No. 24 of 2018 reflects a merit-based selection system that emphasizes managerial competence and professionalism. However, its implementation has not been optimal due to several obstacles, including political intervention after regional leadership changes, limited qualified human resources, and the influence of non-procedural communities. These conditions weaken the effectiveness of regulations in ensuring the integrity and quality of madrasah leadership. In conclusion, strengthening supervision, refining integrity-based selection criteria, and ensuring consistent implementation across all regions are essential to improving the effectiveness of madrasah principal selection in accordance with Islamic management principles.